2021
DOI: 10.1002/cam4.3974
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing online crowdfunding campaigns for patients with kidney cancer

Abstract: Background Cancer patients incur high care costs; however, there is a paucity of literature characterizing unmet financial obligations for patients with urologic cancers. Kidney cancer patients are particularly burdened by costs associated with novel systemic treatments. This study aimed to ascertain the characteristics of GoFundMe® crowdfunding campaigns for patients with kidney cancer, in order to better understand the financial needs of this population. Methods We performed a cross‐sectional, quantitative, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Another change pertinent to our review is the advent of new technologies or policies to potentially alleviate FT, for example, Medicaid expansion through the Affordable Care Act or online crowdfunding platforms such as GoFundMe [ 66 68 ]. Regardless of these steps, however, our review demonstrates the durability of FT as a patient-facing barrier in need of better recognition and management.…”
Section: Discussionmentioning
confidence: 99%
“…Another change pertinent to our review is the advent of new technologies or policies to potentially alleviate FT, for example, Medicaid expansion through the Affordable Care Act or online crowdfunding platforms such as GoFundMe [ 66 68 ]. Regardless of these steps, however, our review demonstrates the durability of FT as a patient-facing barrier in need of better recognition and management.…”
Section: Discussionmentioning
confidence: 99%
“…These findings built on the work of other publications that have examined crowdfunding in urology [ 12 , 16 , 17 ]. For example, Di Carlo et al analyzed 119 urology campaigns from Canada and found that urologic oncology campaigns fundraised more than campaigns raising for urologic benign conditions [ 12 ].…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, in another study, campaigns for prostate cancer were shown to collect significantly less than those for breast cancer [ 16 ]. Thomas et al evaluated 486 GoFundMe ® kidney campaigns and found that among 486 kidney cancer campaigns, only 8% were successful; the median goal was $10,000, the median amount raised was $1450 and the median number of donors was 17 [ 17 ]. We identified considerable heterogeneity in the amount of funding requested and raised by cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…Similar trends apply in the sphere of some rare diseases, where Vassell et al (2020) systematically studied medical crowdfunding campaigns in support of the diagnosis and treatment of Lyme disease, looking for common themes in these narratives. Research in the area of orthopaedics and oncology-kidney cancer in particular-produced similar results, confirming that the allocation of resources (donations) is disproportionally biased towards some diseases, locations and people who know how to master social media, leveraging on their networks to produce a compelling project narrative (Durand et al 2018a;Thomas et al 2021). Food relief campaigns in the United States connected to Covid-19 were also investigated, highlighting once again that a successful output is the result of an exquisite combination of wording, imagery and presence on social media (Zhao et al 2020b).…”
Section: Predictors Of Successful Funding Campaignsmentioning
confidence: 78%